Α-Well-Posedness for Mixed Quasi Variational-Like Inequality Problems. (14th June 2011) - Peng, Jian-Wen; Tang, Jing
Abstract : The concepts ofα -well-posedness, α -well-posedness in the generalized sense, L-α -well-posedness and L-α -well-posedness in the generalized sense for mixed quasi variational-like inequality problems are investigated. We present some metric characterizations for these well-posednesses.